Improvement of ultra-soft soil using prefabricated vertical drains - Chu, J.; Bo, M.W.; Choa, V. (Geotextiles and geomembranes, 2006)
A case study of using prefabricated vertical drains (PVDs) to accelerate the consolidation of an ultra-soft fine-grained soil with high moisture content for a land reclamation project is described in this paper. Large-scale laboratory model tests were carried out to assess the suitability of the selected PVD and the effectiveness of the PVD in the consolidation of the ultra-soft soil. The model tests indicate that the discharge capacity of the drain can decrease substantially after the drain has experienced large deformations. To overcome this problem, PVDs were installed in two rounds. The first round was before the application of surcharge, and the second round was after substantial settlements have taken place. Field instrumentations were utilized to monitor the performance of PVDs during consolidation. The monitored settlement and pore water pressure results are presented and discussed. The study shows that it is effective to use PVD for the consolidation of the ultra-soft soil if special care has been taken in selection and installation of PVD and in fill placement to overcome the difficulties involved in the consolidation of ultra-soft soil.